Cost Analysis of Multimodal Transport on Refrigerated Container. Issue 1 (June 2021) - Meng, Xiangru; Sun, Jianmeng; Wang, Haining
Abstract: Refrigerated container multimodal transport is a long-distance interprovincial transportation, which effectively ensures the quality of agricultural products. The application of refrigerated containers and other means of transportation in the long - distance transportation of perishable agricultural products can reduce the cost of multimodal transport of agricultural products and improve the logistics efficiency. Therefore, it is of practical significance to study the multimodal transport cost analysis of refrigerated containers for perishable agricultural products. The article classifies the applicable goods in refrigerated containers and refrigerated containers; Erishable agricultural products have short shelf life and high damage rate. Refrigerated transportation tools have the particularity; In the cold chain logistics environment, in addition to considering the transportation cost, transit cost and time penalty cost of normal temperature multimodal transport, we should also consider the loss cost of perishable agricultural products in transit and the energy loss cost of refrigerated container refrigeration in transit.